Advances in catalytic conversion of lignocellulosic biomass to ethylene glycol - Enjamuri, Nagasuresh; Darbha, Srinivas (Catalysis Reviews-Science and Engineering, 2024)
Ethylene glycol (EG) is an industrial chemical with multiple applications in polymers, anti-freeze agents, coolants, desiccants and de-icing fluids. It is prepared mainly from fossil feedstock resources. However, its manufacture from renewable sources like lignocellulosic biomass is attractive from the view points of carbon-neutrality and environmental benefits. A few industries have already ventured or committed to produce biomass-derived EG (bio-EG) on a pilot to demonstration scale. At present bio-EG is more expensive than the EG made from fossil resources. Advances are happening in developing more efficient and selective catalysts for the direct conversion of raw biomass and its hydrolysis products (cellulose and glucose) into bio-EG. This review presents the recent advances in catalysts for producing bio-EG.
Keywords: 2-diol; biomass to chemicals; ethane-1; Hydrogenolysis; Lignocellulose; Monoethylene glycol; solid catalyst